2018
DOI: 10.1111/gtc.12639
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of phosphate polymer polyP enhances lactic fermentation in mice

Abstract: In bacteria, a polymer of inorganic phosphate (Pi) (inorganic polyphosphate; polyP) is enzymatically produced and consumed as an alternative phosphate donor for adenosine triphosphate (ATP) production to protect against nutrient starvation. In vertebrates, polyP has been dismissed as a "molecular fossil" due to the lack of any known physiological function. Here, we have explored its possible role by producing transgenic (TG) mice widely expressing Saccharomyces cerevisiae exopolyphosphatase 1 (ScPPX1), which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In this regard, the depletion of mitochondrial polyPs (through the overexpression and the activity of yeast PPX) significantly increased the levels of orthophosphates in the mitochondrial matrix (which is necessary for Ca 2+ binding), thus resulting in a decreased mitochondrial membrane potential and the inhibition of complex I of the respiratory chain (34,35). Thus, the crucial role of polyPs in cell metabolism is clear, as also confirmed in transgenic mice widely expressing the scPPX1 exopolyphosphatase that displayed a reduced mitochondrial respiration in muscles (36).…”
Section: Exopolyphosphatase (Ppx/ppase) Activitymentioning
confidence: 79%
“…In this regard, the depletion of mitochondrial polyPs (through the overexpression and the activity of yeast PPX) significantly increased the levels of orthophosphates in the mitochondrial matrix (which is necessary for Ca 2+ binding), thus resulting in a decreased mitochondrial membrane potential and the inhibition of complex I of the respiratory chain (34,35). Thus, the crucial role of polyPs in cell metabolism is clear, as also confirmed in transgenic mice widely expressing the scPPX1 exopolyphosphatase that displayed a reduced mitochondrial respiration in muscles (36).…”
Section: Exopolyphosphatase (Ppx/ppase) Activitymentioning
confidence: 79%
“…Further investigation has demonstrated that polyP, with an average chain length of 15 or longer, markedly enhances mTOR activation, which phosphorylates downstream molecules [ 7 ]. In transgenic mice expressing a polyP-degrading enzyme derived from budding yeast, the number of litters obtained by intercrossing male and female transgenic mice decreased [ 8 ]. This result implies that polyP may play a beneficial role in fertility.…”
Section: Introductionmentioning
confidence: 99%
“…abnormal levels of polyP have been found in cancer cells [7,8] and in neurons with familial forms (PINK1, LRRK2) of Parkinson's disease [9]. Interestingly, a transgenic mice overexpressing exopolyphosphatase from yeast, which ultimately reduce polyP to very low or almost non-detectable levels of this polymer in all cells, exhibited a phenotype with enhanced lactic acid production and reduced ATP levels [10].…”
Section: Introductionmentioning
confidence: 99%